2014
DOI: 10.1177/1527476414554402
|View full text |Cite
|
Sign up to set email alerts
|

The Politics of Content Aggregation

Abstract: This article deals with the streaming of online video, along a line of comparison to the music industry. Based on qualitative empirical research conducted in Sweden and other European countries, the article focuses on one particular aspect of streamed media, aggregation, since aggregation is central for how streaming is economically, technically, and socially organized. Developing its argument at the intersection of critical media industry studies and economic anthropology, the article argues that online aggre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(20 citation statements)
references
References 26 publications
1
12
0
3
Order By: Relevance
“…These findings also contribute to the policy-oriented academic debate about market concentration in a few industries which can be enriched by the detection of relevant variables in explaining the frequency of Internet use to access music and films online. Indeed, this study is in line with recent studies that also showed the existence of specificities among consumer [7] and [8]. Although the internet adhesion is global wide, it is not the content searched and its consumption behavior.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These findings also contribute to the policy-oriented academic debate about market concentration in a few industries which can be enriched by the detection of relevant variables in explaining the frequency of Internet use to access music and films online. Indeed, this study is in line with recent studies that also showed the existence of specificities among consumer [7] and [8]. Although the internet adhesion is global wide, it is not the content searched and its consumption behavior.…”
Section: Discussionsupporting
confidence: 91%
“…In spite of this fast and global spread of the new platforms to access music and movies and/or series, it is scarce the research about how global is the consumer behavior online. A group of authors [8] examined the consumption of online news video in six countries (Denmark, France, Germany, Spain, United Kingdom and United States) and the findings reflect the power of social media platforms in influencing news consumption habits. Regarding the music online habits, other authors [9] explored whether there are country-specific differences in users' listening behavior on music platforms, based on the data from consumers of 47 countries.…”
Section: Introductionmentioning
confidence: 99%
“…In spite of this fast and global spread of the new platforms to access music and films, it is still scarce the research about how global is the consumer behavior online. A group of authors [6] examined the consumption of online news in six countries (Denmark, France, Germany, Spain, United Kingdom and United States) and the findings reflect the power of social media platforms in influencing news consumption habits. Regarding the music online habits, other authors [7] explored whether there are country-specific differences in users' listening behavior on music platforms, based on the data from consumers of 47 countries.…”
Section: Introductionmentioning
confidence: 99%
“…Internet. This new revolution has changed the way in which information is produced and distributed (STRIPAS, 2009;DARNTON, 2010;ANDERSON, 2011, Blind Review), the spaces in which narratives are accessed and consumed (GILLESPIE, 2014;VONDERAU, 2015) and economic models (GILLESPIE, 2010;VAIDHYANATHAM, 2011;TURROW, 2012), increasing the tension between the limits of autonomy, freedom and heteronomy (CHENEY-LIPPOLD, 2011;NAFUS;SHERMAN, 2014) and provoking debate about security, surveillance, privacy and governance policies (KITCHIN, 2015;MOROZOV, 2015).…”
Section: Introductionmentioning
confidence: 99%